Perbandingan Efisiensi Waktu dan Tenaga Kerja Menggunakan Metode Time Trade Off - Lasty Dinulfy Risfawany K. S.; Josefine Ernestine Latupeirissa; Catherine Mandoa (Jurnal Karajata Engineering, 2025)
In project implementation, there are three main aspects that need to be considered, namely adherence to schedule, expense management, and quality. The Time Cost Trade Off (TCTO) technique is one approach used to evaluate the relationship between time and expenses in construction projects. This study aims to evaluate the time and expense estimates of the project both before and after work hour extensions, as well as to analyse the time and expense estimates of the project before and after total workforce expansion. The data used in this study were obtained through direct observation involving stakeholders in the project to ensure the accuracy and relevance of the data, and will be analysed by applying the Time Cost Trade Off technique. The analysis results indicate that increasing the total workforce is more economical and efficient compared to extending work hours.